Avian high-dose toxicity of cyanobacterial biomass - Kral, Jiri; Pikula, Jiri; Bandouchova, Hana; Damkova, Veronika; Hilscherova, Klara; Misik, Jan; Novotny, Ladislav; Ondracek, Karel; Osickova, Jitka; Mlcakova, Veronika; Pohanka, Miroslav; Skochova, Hana; et al. (Neuro endocrinology letters, 2012)
OBJECTIVES: Previous studies using oral administration of environmentally relevant doses of cyanobacterial biomass containing microcystins (MCs) induced only sub-lethal effects in experimental birds. Therefore, the objective of this study was to obtain data on avian high-dose toxicity of MCs and compute LD50, if possible, following the natural oral route of administration. DESIGN: Responses of birds to single high-dose exposure to MCs were evaluated in fourteen-day old Japanese quail males (Coturnix coturnix japonica) with average body weight of 50 g which were randomly divided into five groups. Birds from four experimental groups were administered 7.5 ml of cyanobacterial biomass suspension containing increasing MCs quantities of 2500, 5000, 10000, and 20000 µg/kg using oral gavage. Controls received an equal dose of drinking water instead of the test substance. Birds were observed for clinical signs of acute toxicity. Survivors were killed on day 5 to obtain body and liver weights. A five-grade semi-quantitative system for histopathological liver damage scoring was used to compare cyanobacterial-biomass-exposed birds against controls. RESULTS: No mortality occurred during the period of five days post exposure in both control and MCs-exposed groups and this high-dose experiment failed to provide data to compute the LD50. Nevertheless, marked sub-lethal effects were recognised in the damage of liver that included dose-dependent changes in the body/liver ratios and morphological changes ranging from mild vacuolar dystrophy to focal liver necroses in the highest exposure group. Hepatic lesions were mainly observed in the pericentral area of the liver. CONCLUSIONS: Though maximum cyanobacterial biomass dose rates that could be administered to birds of the size were used in the present experiment and more pronounced hepatic lesions than after exposure to environmentally relevant doses were observed, birds would probably have survived unless killed for histopathology on day 5 of exposure. These results provide support to previously reported data on sub-lethal effects following exposure to cyanobacterial biomass containing MCs in birds and mortality occurring only in birds under combined action with other stressors.
Keywords: karcinogeny; Dose-Response Relationship, Drug; Hepatocytes; Random Allocation; vztah mezi dávkou a účinkem léčiva; Coturnix; sinice; Male; Cyanobacteria; mořské toxiny; mužské pohlaví; Marine Toxins; Body Weight; Bacterial Toxins; Organ Size; hepatocyty; toxiny kmene Cyanobacteria; velikost orgánu; bakteriální toxiny; zvířata; Microcystins; mikrocystiny; tělesná hmotnost; Carcinogens; Lethal Dose 50; náhodné rozdělení; rizikové faktory; Chemical and Drug Induced Liver Injury; lékové postižení jater; Cyanobacteria Toxins; Biomass; LD50; Risk Factors; biomasa; Animals